2005
DOI: 10.1111/j.1468-2397.2005.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

A dream come true – no more residential care. A corrective note

Abstract: This note is about the attempt by the Australian State and Territory child care and protection systems to do without residential programmes. It traces the process of moving to this position and the historical and policy imperatives that supported this service direction. It also outlines the consequences of the absence of 24 hours‐a‐day 7‐days‐a‐week residential education or treatment programmes for difficult and disturbed young people. It is both a cautionary and corrective note designed to underline the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…There is neither an agreed term nor definition for these children. They have been referred to, for example, as 'troubled and troublesome' (Bullock, Courtney, Parker, Sinclair and Thoburn, 2006) and as the 'most disturbed and difficult children and young people' (Ainsworth and Hansen, 2005). The most conspicuous features of these children's lives are that they have been maltreated or have experienced other acute adversity in their own (family) homes, become looked after as a result (usually in foster homes) but then experience placement breakdown -often because of their challenging behaviour (Boyd, Einbinder, Rauktis and Portwood, 2007;Stanley, Riordan and Alaszewski, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is neither an agreed term nor definition for these children. They have been referred to, for example, as 'troubled and troublesome' (Bullock, Courtney, Parker, Sinclair and Thoburn, 2006) and as the 'most disturbed and difficult children and young people' (Ainsworth and Hansen, 2005). The most conspicuous features of these children's lives are that they have been maltreated or have experienced other acute adversity in their own (family) homes, become looked after as a result (usually in foster homes) but then experience placement breakdown -often because of their challenging behaviour (Boyd, Einbinder, Rauktis and Portwood, 2007;Stanley, Riordan and Alaszewski, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Youth placed into intensive and restrictive settings tend to have complex needs that often require more intensive intervention than can be provided in foster care or standard outpatient mental health treatment (Ainsworth & Hansen, 2005; Davidson-Arad, 2005). These youth have been described as presenting with significant emotional and disruptive behaviors that frequently require psychopharmacological intervention (Breland-Noble et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we need to understand how the acceptability of the treatment milieu to youth and their families (Villani and Sharfstein 1999), placement stability (Dore and Eisner 1993;Penzerro 2003), and appropriateness of the treatment setting (Schoenwald 2002) impact treatment outcomes. It remains, however, that specialized and highly selective residential programs should be a part of a mature system of child protection and care (Ainsworth and Hansen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another study found that while youth in group care start with greater psychological, physical, social, and cultural deficits than those in foster care, they experience faster improvement over the first 15 months, even exceeding foster care on many domains of psychological functioning (Davidson-Arad 2005). Of note, when Australia stopped using residential care programs there was a sense that in many cases foster parents were ill equipped to meet the needs of the more troubled youth (Ainsworth and Hansen 2005), precisely the population most likely to be placed in residential care.…”
Section: Discussionmentioning
confidence: 99%